2013
DOI: 10.1016/j.ecresq.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The Child and Adult Care Food Program and the nutrition of preschoolers

Abstract: Children spend a considerable amount of time in preschools and child care centers. As a result, these settings may have an influence on their diet, weight, and food security, and are potentially important contexts for interventions to address nutritional health. The Child and Adult Care Food Program (CACFP) is one such intervention. No national study has compared nutrition-related outcomes of children in CACFP-participating centers to those of similar children in non-participating centers. We use a sample of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 31 publications
4
82
0
1
Order By: Relevance
“…Existing obesity prevention educational curricula (e.g., the Preschool Obesity Prevention Series) (Miller et al, 2012) seek to enhance children's behavioral regulation skills, but educational materials focused on enhancing children's regulatory skills specific to the childcare context are lacking. CACFP participation has been associated with improved nutritional quality of foods and beverages served in childcare centers (Ritchie et al, 2012) and among low-income children, has been shown to moderately increase consumption of milk and vegetables (Korenman, Abner, Kaestner, & Gordon, 2012). The CACFP recommendations could be further leveraged to help prevent childhood obesity by placing a greater emphasis on the development of training materials for improving childcare providers' use of responsive feeding practices that support children's self-regulation of their energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Existing obesity prevention educational curricula (e.g., the Preschool Obesity Prevention Series) (Miller et al, 2012) seek to enhance children's behavioral regulation skills, but educational materials focused on enhancing children's regulatory skills specific to the childcare context are lacking. CACFP participation has been associated with improved nutritional quality of foods and beverages served in childcare centers (Ritchie et al, 2012) and among low-income children, has been shown to moderately increase consumption of milk and vegetables (Korenman, Abner, Kaestner, & Gordon, 2012). The CACFP recommendations could be further leveraged to help prevent childhood obesity by placing a greater emphasis on the development of training materials for improving childcare providers' use of responsive feeding practices that support children's self-regulation of their energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that CACFP sites may be better informed about nutrition and provide healthier options to children. 13,24 During a 2008 national study, 59% of Head Start centers never served flavored milk, 99% never served other sugarsweetened beverages, and 70% served mostly low-fat or nonfat milk to children. 25 Higher numbers for sugarsweetened beverages were reported by our sample, which included other categories of child care in addition to Head Start.…”
Section: Implications For Practicementioning
confidence: 99%
“…To examine a comprehensive set of outcomes closely related to HS health and nutrition components, based on prior research (Belfield & Kelly, in press; Gormley et al, 2010; Hale et al, 1990; Korenman et al, in press; USDHHS, ACF, 2010), we analyzed six nutrition, weight, and health care receipt outcome variables that were collected at the kindergarten wave. First, we used BMI z -scores, calculated by normalizing BMI to the population based on children's age in months and gender (Centers for Disease Control and Prevention [CDC], 2000).…”
Section: Methodsmentioning
confidence: 99%
“…They found that HS participants showed no differences in weight and nutrition status compared to those who received care from relatives, non-relatives, or parents. Second, Korenman, Abner, Kaestner, and Gordon (in press) compared nutrition-related outcomes (e.g., weight status and food intake) between children in centers (e.g., HS, pre-K, and other preschool centers) participating in the Child and Adult Care Food Program (CACFP) and children in non-participating centers. They found that CACFP participation among low-income children was associated with improved nutrition.…”
Section: Prior Research On Head Start Effects On Children's Health Oumentioning
confidence: 99%